Pore development in terrestrial shale reservoirs: the Permian Lucaogou Formation, Junggar Basin, northwestern China. Issue 6 (18th August 2022) - Jin, Y.; Tian, J.; Han, C.; Liu, H.; Dong, L.; Dan, S.
Abstract: Pore structure is the key factor in determining the development potential of shale reservoirs with a need for more research into mechanisms of pore system development in terrestrial shales. In this study, the pore structure and control mechanisms of typical terrestrial shale reservoirs were described by investigating porosity and permeability under overburden pressure, mercury injection capillary pressure, N2 adsorption, rock pyrolysis analysis, geochemistry and scanning electron microscopy. The results show that: (1) the main pore types in the upper section are quartz and clay intergranular pores, whereas those in the lower section are ferroan dolomite, plagioclase and quartz intergranular pores; (2) clay minerals control the intra-layer pore structure, and quartz minerals control the interlayer pore structure in the upper section, whereas ferroan dolomite provides the largest micron-scale pore size in the lower section; and (3) the micropores of samples with low organic matter content peak at the low maturation stage, whereas the micropores of samples with high organic matter content show an increasing trend from immature to mature stages. The influence of mineral composition and thermal maturity on the development of pore systems in shale reservoirs is an important indicator for future exploration in terrestrial shales. Key points: Factors influencing pore type of a typical terrestrial shale reservoir in the Permian Lucaogou Formation of the Jimsar Depression are inorganic minerals (quartz, ferroan dolomite and clays) and organic matter. Thermal maturity, which controls the development of organic nanopores, peaks at the beginning of the oil window. The pore system in terrestrial shale reservoirs comprises inorganic minerals that control primarily porosity and mature organic matter that control secondary porosity formed during late diagenesis.